Donors of valuable breeding traits of pea (Pisum sativum L.) - Vasylenko, А.; Vus, N.; Bezuglyi, I.; Bezugla, О.; Shevchenko, L.; Kucherenko, Е.; Glyantsev, А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
Analysis of the existing basic collections and identification of the core collections with clearly defined properties are important stages of the plant genetic banks activities. The NCPGRU pea collection has not been studied through this lens. The article presents results of the study of pea (Pisum sativum L. subsp. sativum) accessions as donors of valuable breeding traits for its multipurpose use in agriculture and processing industries. We examined 307 accessions representing the breeding material from the working pea collection of the Laboratory of Grain Legume Breeding of the Plant Production Institute named after V.Ya. Yuriev and the collection accessions of various eco-geographical origins of the National Center for Plant Genetic Resources of Ukraine (NCPGRU). Eleven donors were selected by one or more important agronomic traits in combination with valuable economic characteristics (yield, performance, protein content in seeds, disease resistance (Fusarium wilt and Ascochyta blight)). The cultivars Modus, Efektnyi (multi-flowering (fn fna), leafless (tendril) (af)), Tsarevych (seed shedding resistance (def), leafless (af)), and SL DTR 94-120 (multi-flowering (fn fna), luhansk type of determinancy (d)) were chosen as donors for the grain pea breeding. Orpella (anthocyanin pigmentation of the corolla (A)) and Rezonator (stem length (Le)) were used for the grain/fodder pea breeding; Kharkivskyi Yantarnyi and Banan (seed culinary qualities) – for the groats pea breeding; Stambovyi (parchmentless pods (pv), fascicle stems (fa fas) and Asgrow sead (wrinkled seeds (r), leafless (af), multi-flowering (fn fna)) – for the garden pea breeding; Violena (the rb gene carrier – amylose-free starch) – for the technical pea breeding. All the accessions proved their donor capacities. A qualitatively new input material for practical selection has been derived by means of hybridization with some cultivars (Kharkivskyi Yantarnyi, Banan, Tsarevych, Violena, Asgrow seed). Further study of the NCHRRU pea collection aimed at identification of valuable accessions and creation a core collection is essential.